Efektivitas Latihan Air Tabata dalam Meningkatkan Kecepatan Renang Gaya Bebas 50 Meter - Wing Prasetya Kurniawan; Tomoliyus Tomoliyus; Tri Hadi Karyono (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Appropriate training zone, energy, and distance calculations strongly affect swimmer performance. Strong aerobic and anaerobic skills help swimmers compete. Improving 50-meter freestyle swimming speed requires proper training methods like Tabata water training. This study examines whether Tabata Water Training speeds 50-meter freestyle. His quasi-experimental study uses a pretest-posttest single-group paradigm. A sample of 16 Pradah Swimming Club members was chosen. Active members who had recently competed in regional competitions and gotten constant coaching from licensed instructors were chosen. Such inclusion criteria guaranteed that respondents had extensive training and competition experience, which is essential for study validity. The measurement of 50 meters of swimming time before and after therapy was the tool used. The important variations between pre-test and post-test scores were investigated by means of a paired sample t-test on data. Data normalality was evaluated using a Shapiro-Wilk test before the test. Should the data show a non-normal distribution, a Wilcoxon signed-rank test served as a non-parametric substitute. P 0.05 was the specified significance threshold. The results showed a significant increase in swimming speed after following the training program, with a significance value of 0.000 (<0.05). The average swimming time increased from 46.36 seconds (pre-test) to 42.20 seconds (post-test). In conclusion, Tabata Water Training works well to improve 50-meter freestyle swimming speed. This study offers empirical data that allows coaches to use water-based HIIT techniques as an effective substitute training tool to improve swimmer performance.